2013
DOI: 10.1039/c3ta13285d
|View full text |Cite
|
Sign up to set email alerts
|

Basic aluminum sulfate@graphene hydrogel composites: preparation and application for removal of fluoride

Abstract: Porous composites based on basic aluminum sulfate and graphene hydrogel (BAS@GHG) were prepared via homogeneous precipitation of BAS in GHG, and used as adsorbents for fluoride removal from water.The BAS@GHG composites have a porous structure with a chemically converted graphene three dimensional network coated by a thin layer of amorphous BAS. These composites showed high adsorption capacities of up to 33.4 mg g À1 at equilibrium fluoride concentrations of 10.7 mg L À1 and temperatures of 298 K, higher than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…The maximum percent of removal reached 82 %f or the initial fluorideconcentrationo f1 0mgL À1 .F urthermore, the adsorption was very fast, which is an advantage of BCMP-3 over rare-earth and alumina-based adsorbents. [22] To further study the adsorption behavior of F À onto BCMP-3, two wellknown adsorption models, pseudo-first-ordera nd pseudosecond-order adsorption, were adopted to investigate the adsorptionk inetics. It is well known that an adsorptionp rocess containst hree steps:e xternal liquid membrane diffusion, internal diffusion,a nd surface adsorption.…”
Section: Fluorideanion Adsorptionp Ropertiesmentioning
confidence: 99%
“…The maximum percent of removal reached 82 %f or the initial fluorideconcentrationo f1 0mgL À1 .F urthermore, the adsorption was very fast, which is an advantage of BCMP-3 over rare-earth and alumina-based adsorbents. [22] To further study the adsorption behavior of F À onto BCMP-3, two wellknown adsorption models, pseudo-first-ordera nd pseudosecond-order adsorption, were adopted to investigate the adsorptionk inetics. It is well known that an adsorptionp rocess containst hree steps:e xternal liquid membrane diffusion, internal diffusion,a nd surface adsorption.…”
Section: Fluorideanion Adsorptionp Ropertiesmentioning
confidence: 99%
“…The maximum adsorption capacity of BAS@GHG-2 reaches at pH 7.2. Further increases or decreases the pH, it causes adsorption capacity to decrease about 40% [16]. Similar studies of maxima in acidic pH range have been widely reported [16].…”
Section: Effect Of Phmentioning
confidence: 69%
“…The pH doesn't greatly influence the fluoride adsorption rate, which shows that the adsorption mechanism is chemical ion-exchange in nature. The usable pH range of α-FeOOH@rGO is much wider than the previous studies of fluoride adsorption [15][16][17]. The maximum adsorption capacity of BAS@GHG-2 reaches at pH 7.2.…”
Section: Effect Of Phmentioning
confidence: 84%
“…The developed nanoadsorbent in the present study is a better quality adsorbent with respect to other adsorbents studied in the literature. The nanoadsorbent has significantly higher adsorption efficiency compared with that of other adsorbents at normal drinking water pH range [31,[45][46][47][48][49][50][51][52][53][54]28]. …”
Section: Comparison Of Adsorption Efficiency Of Various Adsorbents Fomentioning
confidence: 99%